2015
DOI: 10.1007/s00383-015-3784-y
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic viral therapy for neuroblastoma cells with Sindbis virus AR339 strain

Abstract: Our results suggested that SINV AR339 was significantly oncolytic against human NB. Thus, SINV showed promise as a novel therapy for treating NB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…SINV infects neurons and induces apoptosis, showing cytotoxicity toward human neuroblastoma cells [8,9]. Previous studies have shown that SINV-induced apoptosis is most efficiently triggered in the presence of structural proteins [16,22], and transient overexpression of SINV structural proteins or UV-inactivated SINV can induce apoptosis in Chinese hamster ovary (CHO) cells and N18 mouse neuroblastoma cells [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SINV infects neurons and induces apoptosis, showing cytotoxicity toward human neuroblastoma cells [8,9]. Previous studies have shown that SINV-induced apoptosis is most efficiently triggered in the presence of structural proteins [16,22], and transient overexpression of SINV structural proteins or UV-inactivated SINV can induce apoptosis in Chinese hamster ovary (CHO) cells and N18 mouse neuroblastoma cells [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…SINV induces apoptosis in most vertebrate cell lines and can be blocked in cells where anti-apoptotic Bcl-2 is expressed [12]. Our previous reports have suggested that human NB cells highly expressing Bcl-2 are resistant to SINV-induced cytotoxicity [7,9]. Thus, cell death signals may be blocked by multiple mechanisms in NB cells, which may, at least partially, compensate for each other.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that naturally occurring oncolytic SIN vectors can be attractive for cancer therapy [67]. Moreover, the oncolytic SINV AR339 strain was evaluated for cytotoxicity and viral growth in five human neuroblastoma cell lines (SK-N-SH, IMR-32, LAN-5, GOTO and RT-BM-1) and in vivo in nude mice implanted with neuroblastoma xenografts [68]. SIN AR339 induced significant cytotoxicity and mRNA levels of the anti-apoptotic genes Bcl-2 and Bcl-xL were increased in LAN-5 and RT-BM-1 cells.…”
Section: Oncolytic Alphavirus Approachesmentioning
confidence: 99%